2018
DOI: 10.2172/1568845
|View full text |Cite
|
Sign up to set email alerts
|

Charged Lepton Flavour Violation using Intense Muon Beams at Future Facilities

Abstract: A submission to the 2020 update of the European Strategy for Particle Physics on behalf of the COMET, MEG, Mu2e and Mu3e collaborations. AbstractCharged-lepton flavour-violating (cLFV) processes offer deep probes for new physics with discovery sensitivity to a broad array of new physics models -SUSY, Higgs Doublets, Extra Dimensions, and, particularly, models explaining the neutrino mass hierarchy and the matterantimatter asymmetry of the universe via leptogenesis. The most sensitive probes of cLFV utilize hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For example the Mu3e experiment may eventually probe µ → 3e down to the level of 10 −16 branching ratio [61]. Moreover the process of µN → eN conversion in nuclei is expected to yield interesting limits in upcoming experiments, including Mu2e [62] at Fermilab and COMET [63] at KEK.…”
Section: Jhep05(2020)039mentioning
confidence: 99%
“…For example the Mu3e experiment may eventually probe µ → 3e down to the level of 10 −16 branching ratio [61]. Moreover the process of µN → eN conversion in nuclei is expected to yield interesting limits in upcoming experiments, including Mu2e [62] at Fermilab and COMET [63] at KEK.…”
Section: Jhep05(2020)039mentioning
confidence: 99%
“…Mu2e is expected to further increase sensitivity by another two orders of magnitude beyond these measurements, culminating an intense program over the next years that may well yield the first discovery of CLFV events. The planned timeline of this experimental program is From Baldini et al 47 shown in Figure 14. If a signal is observed then the complementarity between the three muon transition modes will be a powerful discriminant among the underlying New Physics models.…”
Section: Status and Outlookmentioning
confidence: 99%
“…The current best limits for each process are shown on the left in parentheses, while expected future sensitivities are indicated by order of magnitude along the bottom of each row. From Baldini et al47…”
mentioning
confidence: 99%